The spread of Informal sector in Sub-Saharan Africa: Is there a potential neighborhood effect between countries? - (:unkn) unknown (My University, 2024)
This article focuses on the spread of informal activities within countries of Sub-Saharan Africa(SSA). Using a sample of 41 countries over the period of 2002 to 2018, we estimate a spatialDurbin model in which we use a proximity matrix constructed using the bilateral mobility ofpeople. Our results show that a positive spatial autocorrelation of the informal sector size exists between countries. In other words, within SSA countries, informal activities have spread as a result of complementary interactions between countries considered close on the basis of bilateral mobility of people. The article thus contributes to the empirical literature on the determinants of informality by highlighting a neighborhood influence between SSA countries.
Keywords: African Research